Detecting strongly lensed supernovae at z ∼ 5–7 with LSST. Issue 2 (22nd November 2019) - Rydberg, Claes-Erik; Whalen, Daniel J; Maturi, Matteo; Collett, Thomas; Carrasco, Mauricio; Magg, Mattis; Klessen, Ralf S
ABSTRACT: Supernovae (SNe) could be powerful probes of the properties of stars and galaxies at high redshifts in future surveys. Wide fields and longer exposure times are required to offset diminishing star formation rates and lower fluxes to detect useful number of events at high redshift. In principle, the Large Synoptic Survey Telescope (LSST) could discover large numbers of early SNe because of its wide fields but only at lower redshifts because of its AB mag limit of ∼24. However, gravitational lensing by galaxy clusters and massive galaxies could boost flux from ancient SNe and allow LSST to detect them at earlier times. Here, we calculate detection rates for lensed SNe at z ∼ 5–7 for LSST. We find that the LSST Wide Fast Deep survey could detect up to 120 lensed Population (Pop) I and II SNe but no lensed Pop III SNe. Deep-drilling programs in 10 deg 2 fields could detect Pop I and II core-collapse SNe at AB magnitudes of 27–28 and 26, respectively.